Implementation of Digital Code Lock with Emergency Alarm System - Govardhani. Immadi, M. Venkata Narayana, A. Sree Madhuri, M. Mounika, P. Jyothirmayee, K. Geethasree (International Journal of Advanced Science and Technology, 2020)
Everyone needs security. Now-a-days people are facing many issues related to security. This Digital code lock system implements a password protected lock gives a major difference to daily used locks. Main purpose to implement this lock is for security and cost efficient. The Digital code lock consists of Micro controller, LCD Display, capacitors, Resistors, Keypad, Buzzer, Reset Button, Connecting wires, and Step-down transformer. The state of lock is displayed on the LCD. User can perform operations like opening the lock, closing and also reset the password it means user starts typing from the first key of their password after pressing one or more digits in their password using their keypad. This lock uses micro controller as controlling unit. The lock is protected safely by using password which was set by the user. The lock is opened only when the correct p key is entered by the user by using keypad. Bulb is used to give the status of lock. If password entered by the user is correct then the bulb will ON otherwise it is in OFF condition. If key entered by the user was wrong then the system produces the alarm sound to indicate the key entered by the user is wrong. Thus the Digital code lock system is implemented and ensured.